THE ACHMEA CASES – STORY ON TREATY INTERPRETATION, FORUM COMPETITION AND INTERNATIONAL LAW FRAGMENTATION - Đajić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
In this article the author examines decisions rendered by the UNCITRAL arbitral tribunal in an investment case Achmea v. Slovakia and judgment of the European Court of Justice regarding the compatibility of the investor-State dispute settlement provision in an intra-EU BIT with EU law regarding the Achmea arbitral award on the merits. Given that the ECJ found incompatibility between the two such decision might have wide-ranging consequences. Here the author assesses arguments in different decisions from the perspective of fragmentation of international law, more precisely from the perspective of concepts and arguments developed within the International Law Commission Report on Fragmentation of International Law. While the fragmentation issue was discussed at the early stages of arbitral proceedings it was later abandoned and remained unmentioned by the ECJ. The cause of different takes on the relationship between dispute settlement provisions in intra-EU BIT and EU law could well be described not as a normative but rather as a conflict between different forums. Jurisdictional conflict thus gave rise to the problem of fragmentation in its strict sense – inability of a state to perform two treaty obligations simultaneously.